2023
DOI: 10.3390/insects14060543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Nutrition during the Larval Period on Life History Traits in an Invasive Malaria Vector Anopheles stephensi

Abstract: Anopheles stephensi is an Asian and Middle Eastern malaria vector, and it has recently spread to the African continent. It is needed to measure how the malaria parasite infection in A. stephensi is influenced by environmental factors to predict its expansion in a new environment. Effects of temperature and food conditions during larval periods on larval mortality, larval period, female wing size, egg production, egg size, adult longevity, and malaria infection rate were studied using a laboratory strain. Larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Numerous studies have identified various factors influencing larval mosquito presence in breeding sites, including pH, water temperature, dissolved oxygen, turbidity, soluble solids, salinity, resistance, and nutrition (19)(20)(21). High dry-season temperatures might reduce breeding site availability, as observed in this study (25), and supported by other research (26). This could explain some of the negative breeding sites found during this dry-season study.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies have identified various factors influencing larval mosquito presence in breeding sites, including pH, water temperature, dissolved oxygen, turbidity, soluble solids, salinity, resistance, and nutrition (19)(20)(21). High dry-season temperatures might reduce breeding site availability, as observed in this study (25), and supported by other research (26). This could explain some of the negative breeding sites found during this dry-season study.…”
Section: Discussionsupporting
confidence: 89%